Application of an ultrasound-guided bilateral erector spinae plane block after the Nuss procedure for pectus excavatum in children: a retrospective cohort study with propensity score matching - Shihuan Wu; Jing Wu; Xifeng Zhang (Frontiers Media S.A., 2023)
ObjectiveTo retrospectively analyze the effect of applying an ultrasound-guided bilateral erector spine plane block (ESPB) after the Nuss procedure for surgical repair of pectus excavatum (PE) in children.MethodsThe subjects of the study were patients with severe PE who received the Nuss procedure in our hospital between 1 January 2019 and 30 November 2021. According to different methods for postoperative pain management, the enrolled patients were divided into two groups, the ultrasound-guided ESPB group and the thoracic epidural analgesia (TEA) group. The primary outcome of this study was analgesic drug dosage and the secondary outcome was numerical rating scales (NRSs) between the two groups.ResultsThere was no significant difference between the two groups in terms of demographic, preoperative clinical evaluation, or surgical characteristics (P > 0.05). The catheter duration in the TEA group was significantly shorter than that in the ESPB group (P < 0.05), while the hospitalization time in the ESPB group was significantly shorter than that in the TEA group (P < 0.05). In terms of oral morphine equivalent comparison, the required dose of the TEA group was lower than that of the ESPB group on the 1st and 2nd day after the operation (P < 0.05), and there was no statistical difference between the two groups on the 3rd and 4th day after the operation (P > 0.05). The number of patients with an S-NRS ≥ 7 and D-NRS ≥ 7 in the TEA group at day 1 was lower than that in the ESPB group (P < 0.05). There was no significant difference between the two groups at other time points (P > 0.05),ConclusionAn ultrasound-guided ESPB used in Nuss surgery for children with funnel chest can provide good analgesia for surgery and shorten the postoperative rehabilitation and hospitalization time of patients. It is a safe and effective alternative to TEA.